Efficient purification of unique antibodies using peptide affinity-matrix columns. - Jensen, L; Riise, E; Nielsen, L; Dziegiel, M; Fugger, L; Engberg, J (2004)
Phage display technology was used to identify peptide ligands with unique specificity for a monoclonal model antibody, MK16, that recognises the human multiple sclerosis associated MHC class II molecule DR2 in complex with a myelin basic protein (MBP)-derived peptide corresponding to residue 85-99. Several peptide epitopes were identified and all of them recognised specifically MK16. One peptide, ER6.1, was selected and linked to beaded agarose and demonstrated excellent performance as a peptide affinity chromatography matrix. This epitope matrix was efficient in the purification of MK16 Fab fragments and had no affinity for other antibodies. Using this peptide matrix MK16 IgG could be purified from cell culture supernatants thereby separating MK16 IgG from bovine IgG normally present in the enriched growth media used for such cells. Investigations of the fine specificity of the ER6.1 peptide demonstrated that it recognised a unique epitope within the heavy chain CDR3 region of the MK16 antibody. Thus, variants of MK16 antibody, which had retained the specificity and affinity of the original antibody but had slightly different amino acid composition in the CDR3 region, were not recognised by the ER6.1 peptide.